Bio-inspired poly-DL-serine materials resist the foreign-body response - Zhang, Donghui; Chen, Qi; Bi, Yufang; Zhang, Haodong; Chen, Minzhang; Wan, Jianglin; Shi, Chao; Zhang, Wenjing; Zhang, Junyu; Qiao, Zhongqian; Li, Jin; Chen, Shengfu; et al. (Nature communications, 2021)
Implantation-caused foreign-body response (FBR) is a commonly encountered issue and can result in failure of implants. The high L-serine content in low immunogenic silk sericin, and the high D-serine content as a neurotransmitter together inspire us to prepare poly-DL-serine (PSer) materials in mitigating the FBR. Here we report highly water soluble, biocompatible and easily accessible PSer hydrogels that cause negligible inflammatory response after subcutaneous implantation in mice for 1 week and 2 weeks. No obvious collagen capsulation is found surrounding the PSer hydrogels after 4 weeks, 3 months and 7 months post implantation. Histological analysis on inflammatory cytokines and RNA-seq assay both indicate that PSer hydrogels show low FBR, comparable to the Mock group. The anti-FBR performance of PSer hydrogels at all time points surpass the poly(ethyleneglycol) hydrogels that is widely utilized as bio-inert materials, implying the potent and wide application of PSer materials in implantable biomaterials and biomedical devices. Implantation-caused foreign-body response is a commonly encountered issue and can result in failure of implants. Here, the authors demonstrate that a highly water soluble, biocompatible, and easily accessible poly-DL-serine hydrogel can mitigate foreign-body response.